A mixed-integer linear programming model for hydro unit commitment considering operation constraint priorities - Wu, Xinyu; Wu, Yiyang; Cheng, Xilong; Cheng, Chuntian; Li, Zehong; Wu, Yongqi (Renewable energy, 2023)
Optimizing hydro unit commitment (HUC) has the potential to improve water use efficiency, but should consider complex constraints from power grid, hydropower station and unit operation. When confronted with extreme operating conditions, conflicting constraints cannot be satisfied simultaneously, resulting in no feasible solution. To overcome this drawback, the constraint grading principle is proposed to illustrate how to convert hard constraints into soft constraints and rank them in priority levels. Soft constraints are destroyed according to priority levels from low to high to obtain a feasible solution, simultaneously minimizing the damage degree of soft constraints. Based on the principle, the HUC model considering operation constraint priorities is proposed. When the initial model fails to obtain a feasible solution, low-priority soft constraints are destroyed automatically. Finally, the proposed model is linearized to a mixed-integer linear programming (MILP) model. The commercial solver Lingo is adopted to obtain a feasible solution. The modeling results of Guangzhao hydropower station reveal that: The proposed method can effectively solve the problem of no feasible solution due to conflicting constraints in HUC. Comparing to the penalty function method, the proposed method has better convergence, and strictly reflects the priority of soft constraints. [Display omitted]